2018
DOI: 10.20944/preprints201807.0268.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Sharp Diameter Geometrical Modulation on the Magnetization Reversal of bi-Segmented FeNi Nanowires

Abstract: Controlling functional properties of matter and combine them for engineering a functional device is nowadays a common direction of scientific community. For instance, heterogeneous magnetic nanostructures can make use of different types of geometrical and compositional modulations to achieve the control of the magnetization reversal along with the nano-entities and thus enabling the fabrication of spintronic, magnetic data storage and sensing devices, among others. In this work, diameter modulated FeNi nanowir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Several methods have been successfully developed up to date to synthesize these cylindrical coaxial hetero-nanostructures. Among them, the low-cost template-assisted method can be easily combined with other techniques for the fabrication of hybrid core/shell functional nanomaterials, such as electrochemical deposition [ 9 , 10 ], wet-chemical route and coprecipitation [ 11 , 12 ], atomic layer deposition (ALD) [ 13 , 14 , 15 , 16 , 17 ], and chemical vapor deposition (CVD) [ 18 ]. For this reason, as well as for its high reproducibility and simplicity, this additive fabrication strategy constitutes one of the most widespread methods for the synthesis of one- and two-dimensional (1D and 2D) coaxial nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been successfully developed up to date to synthesize these cylindrical coaxial hetero-nanostructures. Among them, the low-cost template-assisted method can be easily combined with other techniques for the fabrication of hybrid core/shell functional nanomaterials, such as electrochemical deposition [ 9 , 10 ], wet-chemical route and coprecipitation [ 11 , 12 ], atomic layer deposition (ALD) [ 13 , 14 , 15 , 16 , 17 ], and chemical vapor deposition (CVD) [ 18 ]. For this reason, as well as for its high reproducibility and simplicity, this additive fabrication strategy constitutes one of the most widespread methods for the synthesis of one- and two-dimensional (1D and 2D) coaxial nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the modulation in diameter imprinted along the length of magnetic nanowires has become as a promising route to tailor their magnetic properties, allowing for a controlled motion of magnetic domain walls (DWs) and the possibility to manipulate the DW displacement by applying magnetic fields for their implementation in new-generation devices for information storage, logic system and sensors [1][2][3][4][5][6][7][8]. Cylindrical nanowires with modulated diameter and specific compositions are fabricated by different techniques such as the combination of mild and hard anodization processes [9][10][11] or by anodization together with atomic layer deposition (ALD) technique [12][13][14][15][16][17]. The magnetization reversal process of the nanowires can be severely modified by the modulation in diameter, as the modulation might serve as pinning centers for controlling the domain wall movement from one nanowire end to the other [10,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature only a few studies can be found about cylindrical bi-segmented nanowires [14,16,17] and they are mainly focused on soft magnetic materials (e.g. permalloy, FeNi or CoNi) for the synthesis of bi-segmented nanowires with narrow and wide segments ranging between 120 and 450 nm.…”
Section: Introductionmentioning
confidence: 99%